2008
DOI: 10.1080/00365520701745842
|View full text |Cite
|
Sign up to set email alerts
|

Transrectal ultrasonography and magnetic resonance imaging in the staging of rectal cancer. Effect of experience

Abstract: Reader experience had a statistically significant positive effect on the preoperative prediction of tumour involvement of the rectal wall. To obtain high-quality preoperative prediction of rectal cancer T-stage, it is suggested that preoperative TRUS and MRI staging should be supervised by an expert in the colorectal cancer team. In addition to this supervision, the person responsible for staging should be trained through a defined training programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 30 publications
0
20
0
1
Order By: Relevance
“…In one study, the sensitivity and specificity of an expert radiologist were 96% and 74% respectively, while the same figures for a general radiologist were 77% and 40% [20]. …”
Section: Introductionmentioning
confidence: 99%
“…In one study, the sensitivity and specificity of an expert radiologist were 96% and 74% respectively, while the same figures for a general radiologist were 77% and 40% [20]. …”
Section: Introductionmentioning
confidence: 99%
“…The decision to implement these strategies however require accurate staging, which in Europe is more commonly provided by conventional MRI compared with in the United States, where endoscopic ultrasound (EUS) is more widely used (10). Although recent meta-analyses on the sensitivity and specificity of EUS for staging depth of invasion were reported to be between 80% and 96%, and 90% and 98%, and for assessing nodal metastases were 73% and 76%, respectively, inexperienced operators have been shown to provide less accurate staging (11)(12)(13). Overstaging, more common than understaging, has the consequence of subjecting patients to overtreatment.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9]11,15,16 Overstaging can be explained by several reasons. First, Katsura et al reported that peritumoral inflammation can make echogenic layers become hypoechoic, resulting in overstaging of rectal lesions.…”
Section: Discussionmentioning
confidence: 99%